Impact of Various Factors on Color Stability of Fresh Blueberry Juice during Storage - Song, Hyo-Nam (Prev Nutr Food Sci, 2018)
The attractive purple color of blueberries (Vaccinium spp.) is unstable and susceptible to degradation during food processing and storage. The effects of various factors on the color stability of fresh blueberry juice were investigated. Total soluble solid content, pH, and total anthocyanin content were measured. Heating at 30°C and 60°C for 300 min did not influence the color stability, but heating at 100°C drastically decreased it by 33.0%. Sugars decreased color in a concentration-dependent manner. However, glucose and galactose had significantly protective effects on the color disruption than fructose, maltose, and sucrose. Organic acids lowered the color intensity in the order of citric acid> tartaric acid> malic acid> formic acid> acetic acid during 10 days of storage. Color decreased faster during long-term light exposure than in the dark. The color in the dark was kept by 58.7% after 7 weeks, while 48.9% in the light. Color retention was significantly decreased to 93.5% and 93.8% at 4°C and −20°C, respectively, after 7 weeks, while 95.40% at −75°C. We suggest that blueberry juice color can be protected by keeping the extraction temperature below 60°C with the selective addition of glucose, galactose, or citric acid. For long-term storage, it is recommended to use a light-protected container and a deep freezer at −75°C.